Multicultural strip comic as a learning media to improve the caring character in primary school - Nisa Aulia; Wuri Wuryandani (Journal of Education and Learning (EduLearn), 2019)
This research of development aims to produce eligible media and test the effectiveness of multicultural strip comic to improve the caring character of primary school students. It referred to the 10 steps of Borg and Gall.  This research was held on fourth-grade students at five primary schools in Gondokusuman District, Yogyakarta. It consisted of 9 students at the preliminary field testing, 36 students at the main field testing and 62 students at the operational field testing which were divided into two groups, namely experiment class and control class. The technique of data collection involved interviews, observation, scales, and questionnaires. The expert rating scale and the response questionnaire were used to determine the feasibility of the media. The effectiveness of the media was analyzed by the N-Gain score and t-test with a significance level of 0.05. The result showed that multicultural strip comic media is feasible and effective to improve caring character.  This is seen from the N-Gain score and the result of the t-test which obtained a significance value of 0.000 (p ≤ 0.05) which means it can improve the caring character of primary school students.